Reconceptualising 'care' for vulnerable children in the context of HIV/AIDS : a case study of Cotlands. - Guvava, Dorothy Dorica (My University, 2012)
The aim of this study is to investigate how ‘care’ for vulnerable persons in the context of HIV/AIDS has been reconceptualised by Cotlands, a South African non-governmental organisation focusing mainly on childcare. This involves exploring how Cotlands has redefined, re-evaluated and modified ‘care’ so as to deal with the challenges of HIV/AIDS. To this end, the research employed the case study method. Multiple methods including document analysis, participant observation and semi-structured interviews were utilised. The research has shown that care has been reconceptualised to include the provision of holistic care, dependent on the co-ordinated activities and skills of a multidisciplinary team. In addition, the increased use of a community-based model of ‘care’ over the institutional model has been a significant change in the conceptualisation and provision of care in the context of HIV and AIDS. This shift can be attributed mainly to the large number of children rendered vulnerable by the disease. Despite the necessity of this response and an increase in the scope of care provided, the research also demonstrates that this focus shift has had unintended effects including a deterioration of the quality of care these children receive. Recommendations to improve the provision of care include the establishment of a test measure that can assess whether or not Cotlands’ clients have acquired enough understanding of the reason for interventions, the nature of the interventions, and the intended results of the intervention programmes. In addition, Cotlands needs to build a sense of meaning among employees to improve retention, and to include men in its interventions.